The effect of aerobic exercise with pistachio skin extract on the expression of IL-6, IL-1 and TNF-α in heart tissue of obese rats - Mohammad Kazemipour; Hasan Matinhomaee; Parvin Farzanegi (Shahid Beheshti University, 2022)
Background and Purpose: Many environmental factors, including dietary interventions, can moderate inflammation. Previous studies have confirmed that high-fat diets increase the activation of inflammatory markers such as IL-6 in the post-consumption phase. Therefore, the aim of this study was to investigate the effect of aerobic exercise with pistachio green skin extract on the expression of IL-6, IL-1 and TNF-α in the heart tissue of fat-fed rats.Materials and Methods: In this study, 12-week-old female rats weighing between 180 and 220 g were used. Rats were randomly divided into five groups; Positive control (healthy), negative control (obese), exercise, extract, exercise and extract (interaction of exercise and extract). In order to create an obesity model, all rats received 0.5 ml per 100 g of body weight orally by gavage for five weeks, five days a week. The training protocol was performed as moderate intensity training (MET) in the range of 50-60% Vo2max, which includes five training sessions per week (treadmill) with five minutes of warm-up, 20 minutes of activity and five minutes of cooling. On the first day of training, the speed started from 16 m / s and increased 2.5 m/s according to the protocol every week and reached 26 m / s until the last day after four weeks. The extract used in this research was pistachio peel extract at a dose of 60 mg per kilogram. The extract was prepared in liquid and pure form and dissolved with distilled water. Then it was applied by gavage method for four weeks and five times per week.Results: There was a significant difference between the groups in terms of IL-1, TNF-α and IL-6 expression (P = 0.001). Post hoc test showed that there was a significant difference in terms of IL1 and IL-6 expression between obese and healthy groups (P = 0.001). There was a significant difference between the extract group (P = 0.001), the exercise group (P = 0.001) and the exercise + extract group (P = 0.001) with the obese group. There was a significant difference between obese and healthy groups in terms of TNF-α expression (P = 0.002). There was no significant difference in terms of variables between the exercise, extract and exercise + extract groups (P ≥ 0.05).Conclusion: The findings of this study showed that consumption of fatty foods increases the expression of IL-6, IL-1 and TNF-α in the heart tissue of rats. But aerobic exercise and consumption of pistachio skin extract reduced the expression of IL-1 and TNF-α. However, the combination of their combined effects further reduced the expression of IL-1 and TNF-α.